Financial Inclusion, Microcredit Access, and Islamic Social Finance in Enhancing Household Welfare - Khaneishia, Siti; Rahmawati, Yunaita (Inovasi Analisis Data, 2025)
Purpose: It empirically examines the mediating role of financial literacy in the direct and indirect consequences of financial inclusion, microcredit access, and Islamic social finance on household welfare.Method: A quantitative cross-sectional survey design was used to gather data from household heads. An structured questionnaire measured all constructs by standard scales. Data analyses were conducted in two steps wherein the measurement model was verified first, followed by testing the hypothesized direct and mediation effects using regression-based path analysis.Findings: The results indicate that financial literacy is the leading determinant of household well-being and a much stronger influence than direct access to financial resources. Financial inclusion (FI) and access to microcredit show the direct and indirect influences, but for social Islamic finance on welfare are totally mediated by financial awareness. This suggests that the Islamic social instruments are operating not as consumption smoothing transfers, but as transformative inputs into financial capabilities.Novelty: Addressing these gaps and contradictions are among the novelties of this study; it presents a new Integrated Capability-Maqasid al-Shari’ah framework, in which financial literacy is considered the key mediator to convert varied financial resources into welfare opportunities.Implications: The paper offers a blueprint to strategically uplift the developmental power of Islamic finance. It persuasively makes the case for bundling financial education with product delivery and organizing philanthropy, giving Islamic financial institutions the ability to move households from subsistence to sustainable resilience and thus delivering on the ethical aims of fuller human welfare.